The Methology of the Preparation, Valiation and Implementation of Budgets by Polish Municipalities - Leszczyńska-Konczanin, Bogumiła (Studia Oeconomica Posnaniensia, 2016)
The activities of municipalities as the organizations carrying out public duties for the benefit of their communities , is based on fi nancial planning, the rules of which are set out in detail by law. This article presents financial planning as the basis for the financial activities of the local community. There are two types of financial plans - the annual plan (budget) and a multi-year financial forecast covering the budget year and at least three following annual periods. The budget, drawn up by the executive body of local community and approved by the council of the community, contains a statement of total income and expenditure, revenue and financial outflows of the local community relating to the assigned public duties, drawn up in accordance with the budget classification principles. Prior to approval it is assessed by the regional chambers of audit. The actual execution of the tasks must be carried out according to the budget. This means that only scheduled tasks can be implemented no overspend is acceptable . Any tasks involving expenditure above the planned level requires the approval and an amendment to the budget. The degree of implementation of the budget is reported not only to the council of the community but also to the supervisory authorities. Failure to comply with the rules related to the implementation of the budget and the reporting obligations constitutes a violation of discipline in public finance and can be penalized.